(untitled) (Dhaka University Journal of Science, 2021)
The impact of variable fluid properties (viscosity and thermal conductivity) and magnetic dipole on biomagnetic Maxwell fluid past a stretching sheet with slip velocity and heat generation/absorptionhave been studied. Similarity transformation technique is adopted to obtain the self-similar coupled nonlinear ordinary differential equations. Using similarity variable, the basic governing equations with boundary conditions are transformed and solved in bvp4c technique with MATLAB software. The contribution of different pertinent parameters such as viscosity, thermal conductivity and ferromagnetic parameter on the flow profiles with physical quantities are analyzed and examined through graphically. Results shown that with increasing ferromagnetic parameter, slip parameter, Maxwell parameter, velocity decreases but temperature increases. For accuracy of the proposed model to compare our numerical results in numerically and graphically with the previousliterature under some limiting cases and a good agreement is found. Dhaka Univ. J. Sci. 69(2): 109-115, 2021 (July)